Islamic Education According to the Thoughts of Abdurrahman An-Nahlawi and Its Relevance to Contemporary Islamic Education - Saniatun Nisa; Maragustam Siregar (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine Abdurrahman An-Nahlawi's thoughts on Islamic education and examine their relevance to the challenges of contemporary Islamic education. The method used is a qualitative study with a literature study approach, with data sources in the form of An-Nahlawi's works. The results of the study indicate that education according to An-Nahlawi is sourced from the Qur'an and Sunnah as the main foundation in forming a complete Muslim personality, both spiritually, morally, intellectually, and socially. According to him, the Islamic education curriculum must be in harmony with human nature, flexible, realistic, and adapted to the conditions of students. An-Nahlawi also formulated psychologically based educational methods, such as the hiwar method, cerita, ibrah, and exemplary. The relevance of his thoughts to today's education lies in his comprehensive, integrative, and adaptive approach to developments in the era of globalization, while still maintaining Islamic values as the main foundation. This research makes an important contribution to efforts to re-ground the principles of authentic Islamic education amidst the challenges of the globalization era.